Sosialisasi dan Pelatihan Akuntansi bagi Pesantren dalam Rangka Meningkatkan Tata Kelola Pondok Pesantren - Misni Erwati; Muhammad Ridwan; Dewi Fitriyani; Lutfi; Wiwik Tiswiyati (Studium: Jurnal Pengabdian Kepada Masyarakat, 2022)
In comparison to other educational institutions, Islamic Boarding School or Pesantren is a community education institution that provides a more in-depth Islamic religious education. It also use financial management to keep track of all financial transactions in order to practice good governance. As a result, the team engaged in community service activities with the aim of enhancing the understanding and abilities of its financial management in compliance with Islamic Boarding School Accounting Guidelines issued by the Institute of Indonesia Chartered Accountants and Bank Indonesia. The community services were held on Saturday, September 7, 2019, at the Al Jauharen Islamic Boarding School, which is located in Tanjung Johor, Pelayangan Regency, Jambi City. Lectures were carried out in the form of socialization and training for pesantren administrators. The participants’ enthusiasm demonstrated their curiosity to learn more about accounting for Islamic boarding schools.